PENGEMBANGAN MODEL BIMBINGAN PERSIAPAN UJIAN PENGETAHUAN MAHASISWA PROGRAM STUDI PENDIDIKAN PROFESI GURU DALAM JABATAN DI LPTK IAIN PONTIANAK - Ana Rosilawati; Budiyono Budiyono; Ahmad Murtadha; Ahmad Kamaludin (Journal of Research and Thought on Islamic Education (JRTIE), 2022)
This research was conducted based on the results of the PPG/IAIN Pontianak Study Program student exam results in 2021, which are still below the minimum passing standard of 75%. Coaching knowledge testing and guidance through the development model are two examples of efforts that can be made. The aims of this study were 1) to find out the module development model for the guidance program preparation for student knowledge test for students in the in-service teacher profession program at LPTK IAIN Pontianak stage 1 in 2022, 2) to validate the module development model for the guidance program preparation for student knowledge test for the in-service teacher profession program at TTIs IAIN Pontianak phase 1 in 2022, and 3) to implement the guidance program module for in-service teacher professional education at LPTK IAIN phase 1 in 2022. This study uses the Borg and Gall model of research and development (RD). The results of this study are: the model developed is in the form of a module, showing qualifications worthy of being used in the learning process for preparation for knowledge exams; validation of the model developed in the form of a module from the feasibility of the curriculum in the "very eligible" category; the feasibility of the field of study in the "decent" category; and the results of instructional design feasibility in the "feasible" category. As for implementation, the use of the development model includes learning activities for pedagogical material and learning activities for subject matter. While the value of learning outcomes after using the development module gets an average score of 77 for PAI and 74 for madrasah and is in the "good" category.This research was conducted based on the results of the PPG/IAIN Pontianak Study Program student exam results in 2021, which are still below the minimum passing standard of 75%. Coaching knowledge testing and guidance through the development model are two examples of efforts that can be made. The aims of this study were 1) to find out the module development model for the guidance program preparation for student knowledge test for students in the in-service teacher profession program at LPTK IAIN Pontianak stage 1 in 2022, 2) to validate the module development model for the guidance program preparation for student knowledge test for the in-service teacher profession program at TTIs IAIN Pontianak phase 1 in 2022, and 3) to implement the guidance program module for in-service teacher professional education at LPTK IAIN phase 1 in 2022. This study uses the Borg and Gall model of research and development (RD). The results of this study are: the model developed is in the form of a module, showing qualifications worthy of being used in the learning process for preparation for knowledge exams; validation of the model developed in the form of a module from the feasibility of the curriculum in the "very eligible" category; the feasibility of the field of study in the "decent" category; and the results of instructional design feasibility in the "feasible" category. As for implementation, the use of the development model includes learning activities for pedagogical material and learning activities for subject matter. While the value of learning outcomes after using the development module gets an average score of 77 for PAI and 74 for madrasah and is in the "good" category.